Product standardization through SNI as a form of consumer protection in Indonesia - Valensia, Valensia; Sartono, Tulus (Legality : Jurnal Ilmiah Hukum, 2020)
Business relationships formed between consumers and business actors allow disputes to arise as a result of damage or defects and losses. This research will examine issues regarding the regulation of consumer legal protection of SNI compulsory products in Indonesia. The research method used is a normative legal research method. This research shows that legal protection for consumers can be created by the existence of regulations related to SNI obligations. Some arrangements that provide preventive protection to the interests of consumers, include Law No. 20 of 2014 concerning Standardization and Conformity Assessment and Law No. 8 of 1999 concerning Consumer Protection as an effort to protect the law for consumers. The law also protects consumers after an event has occurred against violations committed by business actors with acts of civil lawsuits, criminal suits, lawsuits using the Consumer Protection Act, as well as the imposition of sanctions on business actors.